Membrane transporter progressive ankylosis protein homologue (ANKH/Ank) partially mediates senescence-derived extracellular citrate and is regulated by DNA damage, inflammation, and ageing - James, Emma Naomi; Teh, Muy-Teck; Li, Yufeng; Wagner-Bock, Christine; Al-Khateeb, Zahra Falah; Karen-Ng, Lee Peng; Roberts, Terry; Synchyshyn, Linnea; Lewis, Amy; O’Loghlen, Ana; Silver, Andrew; Michael-Titus, Adina Teodora; et al. (Frontiers in Aging, 2025)
IntroductionA considerable body of recent evidence supports citrate transport as a major regulator of organismal lifespan and healthspan. Citrate accumulates outside senescent cells in vitro and in vivo. However, the detailed mechanism of senescent cell extracellular citrate (EC) accumulation is not clear.MethodsEC following various drug and cytokine treatments was measured in human fibroblast and keratinocyte conditioned medium by gas chromatography/mass spectroscopy and liquid chromatography/mass spectroscopy. Membrane transporters in similar human fibroblasts cultures were measured by western blotting and more extensively by reverse transcription and quantitative polymerase chain reaction (qPCR) in human fibroblasts, keratinocytes, myoblasts, adipocytes and astrocytes. Mouse tissues were tested for senescence markers and by qPCR, immunofluorescence and immunoFISH telomere associated foci (TAF) staining. Cytokine levels in conditioned medium were measured by the enzyme-linked immunosorbent assay and in mouse brain tissue and plasma samples using the V-PLEX proinflammatory panel 1 mouse kit.Results and DiscussionWe show here that EC is partially mediated by a newly described plasma membrane citrate transporter ANKH/SLC62A1 (progressive human ankylosis -ANKH) in senescent fibroblasts. Analogous to interleukin 6 (IL-6), EC and/or ANKH are regulated by telomere dysfunction, the p38 mitogen-activated kinase axis, transforming growth factor beta and p53, but in contrast not by steroids, sodium butyrate, or Ataxia Telangiectasia Mutated (ATM). ANKH was upregulated in other senescent cell types relevant to ageing but not keratinocytes. In contrast, EC and ANKH were inhibited by interleukin 1α (IL-1α) in dividing and senescent fibroblasts, accompanied by an increase in IL-6 secretion. Loss- and gain of function mutations of ANKH/Ank are associated with disease and interestingly, Ank is also downregulated in both aged mouse liver and brain tissues in parallel with increased senescence markers and several cytokines, suggesting that inflammatory cytokines could inhibit EC production in vivo. These data identify ANKH/Ank as a novel regulator of senescence-derived EC in both humans and mice.